Efecto in vitro de una sustancia alcaloidea aislada de Amphime don viridis (Porifera) sobre promastigotes de Leishmania mexicana - Marchán M., Edgar; Arrieche, Dwight; Henríquez, William; Cresente, Oscar (Revista de Biología Tropical, 2000)
The dose dependent antiproliferative effect of an alkaloidal substance extracted from the sponge Amphimedon viridis was tested on Leishmania mexicana promastigotes. Sponges were collected in Isla Larga, Venezuela (10°20'20" - 10°24" N, 64°19' - 64°22' W), cut and dipped in methanol for vacum filtering extraection every 24 hr. The aqueous extract was separated by chromatography over silica gel. The parasites were from the Venezuelan NR strain. Their growth rate was reduced by 50 % with a dose of 10 μg/ml in 48 hr, whilst concentrations of 30 and 40 μg/ml induce leishmanicidal action after 110 and 20 min, respectively. Lysis is preceded by an immediate increase in cellular volume associated with progressive damage of cellular content and the destruction of organelles. These findings suggest that one important factor associated with the antiproliferative effect of this alkaloidal substance on L. mexicana promastigotes is the loss of the plasma membrane selective permeability.